Recent Advanced Ultra‐Wide Bandgap β‐Ga2O3 Material and Device Technologies - Sihan Sun; Chenlu Wang; Sami Alghamdi; Hong Zhou; Yue Hao; Jincheng Zhang (Advanced Electronic Materials)
Abstract Gallium oxide (Ga2O3) is an emerging ultra‐wide bandgap (UWBG) semiconductor material that has gained significant attention in the field of high voltage and high frequency power electronics. Its noteworthy attributes include a large bandgap (Eg) of 4.8 eV, high theoretical critical breakdown field strength (EC) of 8 MV cm−1, and saturation velocity (νs) of 2 × 107 cm s−1, as well as high Baliga figures of merit (BFOM) of 3000. In addition, Ga2O3 has the advantages of large‐size substrates that can be achieved by low‐cost melt‐grown techniques. This review provides a partial overview of pivotal milestones and recent advancements in the Ga2O3 material growth and device performance. It begins with a discussion of the fundamental material properties of Ga2O3, followed by a description of substrate growth and epitaxial techniques for Ga2O3. Subsequently, the contact technologies between Ga2O3 and other materials are fully elucidated. Moreover, this article also culminates with a detailed analysis of Ga2O3‐based high voltage and high frequency power devices. Some challenges and solutions, such as the lack of p‐type doping, low thermal conductivity, and low mobility are also presented and investigated in this review.